STRESS IN WORKING WOMEN: AN OCCUPATIONAL THERAPY PERSPECTIVE - Shahi , Saqueba; Ali, Nazia (International Journal of Psychosocial Rehabilitation, 2025)
Background: women who are employed have certain occupational pressures that harm their physical and mental health, job performance and standard of living. Because of the increase in stress-related conditions in females who work, different healthcare areas, including occupational therapy, now need to offer proved intervention solutions.Objective: this literature review studies what is currently known about stress management interventions designed for working women and assesses how well these programs are carried out, whether they are effective and what research gaps remain in this field from 2020-2025.Methods: the search was made by relying on multiple databases and including all relevant papers reviewed during 2020-2025. Articles about occupational therapy interventions for stress reduction in employed women were examined for what was done, the outcomes and how effective it was.Results: twenty-five studies met inclusion criteria, revealing significant evidence for occupational therapy interventions in stress management for working women. Key intervention approaches include cognitive-behavioral techniques, mindfulness-based interventions, occupational balance strategies, and workplace modification programs. Statistical analysis shows moderate to large effect sizes (cohen's d = 0.526-0.78) for stress reduction interventions.Conclusion: occupational therapy makes evidence-based interventions for helping working women manage stress using methods focused on all aspects of their lives, jobs and workplace.